Is nullity for Glutathione S-transferase genes GSTT1 and GSTM1 protective against leprosy? - Graca, Carla Renata; Cordeiro-Soubhia, Rosa Maria; Tonelli-Nardi, Susilene Maria; Belini Junior, Edis [UNESP]; Bonini-Domingos, Claudia Regina [UNESP]; Gauch, Camila Ravazzi; Da Silva Da Rocha, Elisabeth Martins; Paschoal, Vania Delarco; Kouyoumdjian, Joao Aris; De Souza Baptista, Andrea Regina (Lepra, 2016)
Introduction: Leprosy is a slow and progressive infectious disease caused by Mycobacterium leprae. The generation of free radicals called reactive oxygen species (ROS), which promote destruction of the bacillus within macrophages, is an effective defence mechanism developed by the host. In parallel, the glutathione S-transferase (GST) multifamily of enzymes constitutes an important antioxidant system for ROS detoxification and protection against toxicity. Therefore, GST null genotype individuals could reduce the detoxification of ROS, increasing host effectiveness for M. leprae destruction. Objectives: To evaluate polymorphisms in the GSTT1 and GSTM1 genes as human leprosy susceptibility modulators. Methods: GSTT and GSTM1 polymorphisms were genotyped by a multiplex polymerase chain reaction (PCR) in 218 leprosy patients and 244 non-leprosy subjects (control group). Results: The occurrence of the GSTT1/GSTM1 null genotype was significantly higher among control subjects than amongst leprosy patients (P = 0.01). The GSTT positive genotype frequency was significantly increased in leprosy patients when compared with control subjects (P = 0.01). Conclusions: The results suggest that GSTT1/M1 nullity may play an important role in leprosy pathogenesis. Significance: Despite these findings, further studies will be necessary to ascertain the exact role of these genes in leprosy and to design any future prevention measures or contributions to drug therapy.
Keywords: Glutathione S-transferase; Leprosy; Reactive Oxygen Species; Mycobacterium leprae